Psycho-Emotional, Regulatory, and Environmental Factors that Affect the Performance of English Teaching Students and Professors in Oral Tests at the UCR Atlantic Branch - Sanabria Mora, Esteban (2023)
The performance of students and professors during a summative tribunal oral test is not only influenced by the linguistic and communicative skills of the participants, but also by some factors unrelated to proficiency in the language. Therefore, this article summarizes the research that was carried out at the Atlantic Branch of the University of Costa Rica in the second semester of 2013, which included professors and students of the Oral Communication II, IV, and VI courses of the English Teaching major of its three campuses. Moreover, the objective of this study was to identify the psycho-emotional, regulatory, and internal and external environmental factors that could negatively influence the students and professors of this major when participating in summative oral tests. Regarding the approach, this research followed a quantitative one and considered every type of factor as dependent variables, with a descriptive purpose. All students and professors in these courses were surveyed between September and October 2013. The main results show that both students and instructors are affected by these three types of factors, mainly students, who claim that their performance is influenced by factors such as fear, sweating, heavy breathing, classroom ventilation, and the time that the test takes. For their part, it is concluded that professors are mostly affected by regulatory factors such as the total duration of the test application, as well as aspects such as exhaustion. Hence, the main recommendation derived from this research, for both students and professors, is to review in detail the student academic regime regulations (Reglamento de Régimen Académico Estudiantil, in Spanish) to know in depth their rights when it comes to evaluation (in the case of students) and avoid counterproductive evaluation practices (in the case of professors).